Cancer/testis (CT) antigens are expressed in fetal ovary - Nelson, Peter T. (Academy of Cancer Immunology, 2007)
Cancer/testis (CT) antigens are named after their expression pattern as they are typically present in various types of tumors and in the germ cells of normal adult testis. Adult ovarian tissue is usually reported to be CT antigen negative. Based on the differences in female versus male gonadal development, the ovarian counterpart of the most predominant CT antigen positive testicular germ cells are not prevalent in the adult ovary. Hence, we analyzed the protein expression of several CT antigens in fetal ovary by immunohistochemistry with various monoclonal antibodies (mAbs) previously generated by our group. The mAbs used were: MA454 (MAGE-A1), M3H67 (MAGE-A3), 57B (MAGE-A4), CT7-33 (CT7/MAGE-C1), and ES121 (NY-ESO-1). All mAbs showed some immunopositivity in fetal ovarian germ cells. The most intense staining was seen with mAbs M3H67, 57B, and CT7-33 during weeks 16 – 23 of gestation. The most prevalent cells stained were oogonia, with only focal staining of oocytes of the primordial follicle. We conclude that CT antigens are regularly expressed in fetal ovarian germ cells and might play an important role in male and female germ cell biology.